KDM4B under hypoxia: a new targetable pathway for epithelial ovarian cancer? - Chung, Vin Yee; Huang, Ruby Yun-Ju (Translational Cancer Research, 2017)
Ovarian cancer is one of the most fatal gynecological malignancies in women. In 2012, global statistics ranked ovarian cancer as the seventh most common cancer and the eighth most common cause of cancer-related death in women worldwide (1). The lethality is mainly attributed to late presentation of the disease, rapid and widespread metastases in the peritoneal cavity, and high occurrence of disease relapse due to chemoresistance (2). The most common form of ovarian cancer, epithelial ovarian cancer (EOC), is divided into type I and II. The latter comprises the most commonly diagnosed subtype—high-grade serous adenocarcinoma, which is usually genetically unstable and highly metastatic.